Uso de imunossupressores por sondas enterais: avaliação da técnica de administração, efetividade e segurança - Silva, Renan Morais e (2021)
The administration of drugs through enteral tubes is a daily challenge in clinical practice. There are two aspects: one of the health professionals who are faced with factors such as choosing the appropriate dosage form, correct timing of the diet and medication, osmolarity of the solution or suspension, proper handling of the dosage form and adverse effects at the time of selection of this via; and the other of the patient, generally of high complexity, with impossibility of oral feeding or dysphagia, and who need both nutritional therapy and adequate pharmacotherapy. In organ transplantation, there are still other aggravating factors: the lack of immunosuppressants in liquid dosage forms, drugnutrient interactions that reduce the absorption and bioavailability of immunosuppressants, in addition to the risks of toxicity and rejection of the transplanted organ. The objective of this research was to investigate the use of solid dosage forms of immunosuppressants by enteral tubes and their relationship with the effectiveness and safety of this pharmacotherapy. We divided our study into two stages: experimental and clinical study in the format of a case series. The prospective, analytical and quantitative experimental study evaluated the immunosuppressive drugs that are available in solid dosage forms and present in the Clinical Protocols and Therapeutic Guidelines for Immunosuppression in Liver or Kidney Transplantation, without active registration of liquid dosage form at ANVISA and standardized by the Walter Cantídio University Hospital. Dispersion tests were carried out in oral dosing dispensers (Oralpack®). The assays were carried out in the Physical-Chemical Control Laboratory of the Pharmacy School of the Federal University of Ceará. The descriptive, retrospective, quantitative and exploratory clinical study, in the format of a case series, using data from the Pharmacotherapeutic Follow-ups of kidney or liver transplant patients who used immunosuppressants by enteral tubes during their hospitalization between 2017 and 2018 at the Walter Cantídio University Hospital was carried out. We selected 4 clinical cases of patients who used at least one of the immunosuppressants studied, by enteral tubes, for a minimum period of 5 days. Sociodemographic data, information about the transplant, past and current pathological history, pharmacotherapy of previous use and during the period of hospitalization, use of enteral tube and other routes of administration, clinical and laboratory evolutions, and clinical outcomes were retrieved, considering the data from the period of hospitalization of these patients until the outcome of improved hospital discharge, replacement by parenteral immunosuppressant or death. Statistical analysis was descriptive and inferential, considering that there was no difference in the effectiveness and safety of immunosuppressive therapy when it is administered by enteral tubes or by mouth. In all, 21 dispersion tests were performed considering 7 different medications and 5 drugs, where only the sodium mycophenolate presentations did not disperse in the oral dosing syringes. The mean length of hospital stay was 38.3 ± 9.2 days. Patients had a mean duration of transplantation of 3.71 ± 4.3 years, all of whom used a nasoenteral tube during follow-up with a mean duration of use of 21.5 ± 6.2 days. The mean age among patients was 64.75 ± 9.18 years. A total of 92 drugs were used, with 578 DRP and 430 MRI identified. It was observed that the recently transplanted patients presented more discrepant results in terms of serum levels of tacrolimus, possibly due to drug interactions, dose groping, greater number of drugs and adaptation to the immunosuppressive regimen. However, there was no statistically significant difference between the parameters evaluated for effectiveness and safety in the comparison between oral and enteral tubes. Studies with a larger number of patients and/or more MRP and MRI are needed to verify this behavior and optimize this pharmacotherapy.